Crosstalk in misaligned free space optical interconnects: modelling and simulation - Nedal Al-Ababneh (Institute of Advanced Engineering and Science, 2019)
We introduce convenient model and an optimization scheme to optimize the signal-to-crosstalk ratio (SCR) in a free space optical interconnects (FSOIs) system that uses microlenses with finite circular apertures. In this model, we consider both the stray light crosstalk and the crosstalk due to the diffraction at the microlens apertures to evaluate the SCR. Using cylindrical form of Collins diffraction integral and the Laguerre–Gaussian (LG) beam model, we derive an approximate closed form formula for the optical field of a multimode LG beam propagating through circular apertured FSOIs by expanding the hard edge circular aperture function of the microlens in terms of complex Gaussian functions. The analyses indicate that the size of the detector is an important factor to optimize the SCR for both the apertured and the unapertured misaligned FSOIs system. The effect of higher order mode of the laser source on the SCR is also considered.